The relationships of emotional expressiveness, positive affect, and negative affect with dark triad personality traits (Machiavellianism, narcissism, Psychopathy) - S Amiri; F Sepehrian Azar (فصلنامه ابن سینا)
Background: In recent years, there has been increased interest in a set of traits which are referred as dark triad personality traits including Machiavellianism, narcissism, and psychopathy. The aim of this study was to investigate the relationships of emotional expressiveness, positive and negative affect with dark triad personality traits.